PELAKSANAAN TUGAS KEPALA SYAHBANDAR DALAM PEMBERIAN SURAT PERSETUJUAN BERLAYAR (SPB) PADA KANTOR KESYAHBANDARAN DI KOTA PEKANBARU - Raja Muhammad Rasid; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Raja Muhammad Rasid (1201112415). Duties Head Of The Issuance Agreement Port Officer Sail (SPB) On Harbour Master Office In The City Of Pekanbaru. Supervisor : Dra. Ernawati, M.Si.Under Article 6 of Law No.17 of 2008, the type of transport in the waters consist of sea transport, river and lake transport and ferry transport. In accordance with Article 219 of Law No.17 of 2008, to conduct any ocean freight shipping (vessel) shall require approval Sailing / Anchored (SPB) is issued by the harbormaster to be sailing or docked. In order to obtain a Certificate of Approval Sailing/Anchored (SPB), the ship will sail must meet the requirements that the terms seaworthiness ship.In theory Duties, Simanjuntak explained that the implementation of the duty of each individual is influenced by several factors which can be classified into three groups: individual competency, organizational support and management support .The method used in this research is qualitative research. With the technique done of snowball sampling, the key informant in this study. In this study, the informant is the Head Office and the Port Authority Harbour Master Class III In The City Of Pekanbaru, Head of Sub. Administration, Head of Legal Status and certification of ships, Kasi Kesber, Guard and Patrol, and Kasi Enterprises Lala and Ports and then analyze and process the data .Based on the research and discussion that researchers do in the field, it was found that the execution of tasks of the Head of the Harbor Master in the Issuance of Approval Sail (SPB) At Office Harbor Master in the city of Pekanbaru has not been implemented to the fullest, it is in because of limited support infrastructure in the field, the lack of human resources and lack of awareness of the laws that affect the execution of tasks Harbor Master.Keywords : Individual competence, Organizational Support, ManagementSupport